Symmetric versus asymmetric tibial components: A systematic review of comparative studies - Bassem I. Haddad; Alaa Tarazi; Raha Alzoubi; Mahmmud S. Alqawasmi; Abdullah Ammar; Zinah Kalare (Journal of Orthopaedic Surgery and Research)
Abstract Background Total knee arthroplasty (TKA) is a widely performed procedure that significantly enhances patients’ quality of life by reducing pain and improving daily function. While the traditional tibial plate design used in TKA has been symmetrical, there has been a recent trend towards using asymmetrical designs. Our study aimed to compare symmetrical and asymmetrical tibial designs, focusing on outcomes related to overhang, malrotation, and tibial coverage. Methods This systematic review was conducted in accordance with PRISMA guidelines. A comprehensive search of PubMed, Scopus, Web of Science, and Cochrane databases was carried out up to January 22nd, 2024, to identify comparative studies on symmetrical and asymmetrical designs, as well as those reporting postoperative functional and clinical outcomes. The risk of bias in the included studies was evaluated using the Newcastle-Ottawa Scale (NOS). Results This systematic review included 587 patients from seven comparative studies that met the inclusion criteria. Our findings indicate that asymmetrical tibial components generally provided better outcomes in terms of tibial coverage, malrotation, and overhang. Asymmetrical designs provided greater tibial coverage and reduced posterolateral overhang compared to symmetrical designs, which is essential for minimizing complications like soft tissue irritation and patellar maltracking. Additionally, asymmetrical components were associated with less severe tibial malrotation. Conclusion This systematic review showed that asymmetrical tibial implants offer better tibial coverage, with less overhang and fewer rotational issues compared to symmetrical implants. As a result, asymmetrical designs in TKA may lower complication rates, enhance patient satisfaction, and improve quality of life post-surgery.